2006
DOI: 10.2355/isijinternational.46.1403
|View full text |Cite
|
Sign up to set email alerts
|

Production of Pig Iron from Magnetite Ore–Coal Composite Pellets by Microwave Heating

Abstract: Magnetite ore-coal composite pellets with about 10, 15 and 20 mm diameter were rapidly smelted to produce pig iron by microwave heating in N 2 gas. A microwave generator with 5 kW maximum power at 2.45 GHz was employed. Carbon content in pig iron was about 2 mass% near the liquidus line in the Fe-C system. Slag was easily separated from pig iron. By XRD analysis it is realized that the reduction of magnetite started at about 800°C and was completed to be pig iron at about 1 350°C. The heating rate of pellets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
56
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 11 publications
6
56
0
1
Order By: Relevance
“…Additionally, for the carbon composite iron ore agglomerates, a great deal of research was done on the reduction and melting behavior, [12][13][14][15][16] effects of the carbon content 17) and the atmospheric gas composition 18) on the reduction behavior, the cold strength enhancement mechanism, 19) the mechanism of pig iron making from magnetite ore pellets containing coal at low temperature 20) and by microwave heating. 21) Furthermore, great attention has been paid to mechanical milling of iron oxide and carbonaceous material in recent years. It was found that the mixing state and the structure of composite significantly influenced reduction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, for the carbon composite iron ore agglomerates, a great deal of research was done on the reduction and melting behavior, [12][13][14][15][16] effects of the carbon content 17) and the atmospheric gas composition 18) on the reduction behavior, the cold strength enhancement mechanism, 19) the mechanism of pig iron making from magnetite ore pellets containing coal at low temperature 20) and by microwave heating. 21) Furthermore, great attention has been paid to mechanical milling of iron oxide and carbonaceous material in recent years. It was found that the mixing state and the structure of composite significantly influenced reduction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…We have focused on the microwave heating as a new heating source for iron making. [1][2][3][4] Ishizaki et al 2) have produced the highly-pure pig iron from the carbon composite iron ore pellet composed of the mixture of magnetite ore (Romeral) and coal (Robe River) powders by means of a 2.45 GHz microwave furnace. The temperature reached 1 350°C ca.…”
mentioning
confidence: 99%
“…Apesar de ser fácil adaptar uma balança ao forno, podendo acompanhar de maneira contínua a variação da massa da amostra durante o aquecimento, esse recurso é raramente utilizado. As pesquisas com micro-ondas na redução de minério de ferro concentram-se em reduzir o tempo de redução em relação ao consumido em forno elétrico [6]; em reduzir a emissão de CO2 bem como a conservação de energia em um processo de redução carbotérmica comparando-o com alto-forno [7]; nas mudanças das fases do ferro formado variando os níveis de potência irradiada de micro-ondas [5]; do efeito da variação da freqüência de micro-ondas de 2,45 GHz para 30 GHz [8] e da utilização de outras fontes de carbono para substituírem os redutores convencionais [1]. Além disso, devido à diminuição de recursos energéticos e a introdução de leis ambientais mais rigorosas, a busca de novos processos de produção de aço e ferrogusa tornaram-se estratégicos.…”
Section: Introductionunclassified